Sweroside Modulates Oxidative Stress and Neuroplasticity-Related Gene Expression in Scopolamine-Treated Zebrafish - Brinza, Ion; Stache, Bogdan Alexandru; Mihasan, Marius; Gorgan, Dragos Lucian; El Raey, Mohamed A.; El-Kashak, Walaa; Eldahshan, Omayma A.; Hritcu, Lucian (CNS & Neurological Disorders - Drug Targets, 2025)
BackgroundA major issue with neurodegenerative diseases is cholinergic depletion, the development of oxidative stress, and the reduction in the ability to control the expression of genes involved in the regulation of neurogenesis. The most widespread neurodegenerative disease is Alzheimer's disease (AD). Current treatments are not able to improve the symptoms of the disease. Thus, selecting or creating a safe and effective drug is very important.ObjectiveIn this context, the potential of sweroside (Swe) to regulate acetylcholinesterase (AChE) activity, malondialdehyde (MDA) level, and bdnf, npy, egr1, nfr2a, and creb1 gene expression in the scopolamine (Sco)-induced zebrafish model of cognitive impairment was investigated.MethodsSwe was administered daily for 16 days chronically to zebrafish at concentrations of 1 µg/L, 3 µg/L, and 5 µg/L whereas Sco (100 µM) was given to zebrafish for 30 min.ResultsExposure to Swe decreased AChE activity and MDA level along with upregulating of gene expression in the brain of the Sco-induced zebrafish model.ConclusionOverall, our findings suggested that Swe has a positive role in the cholinergic system activity and brain antioxidant status and showed for the first time that it can restore the downregulated expression of bdnf, npy, egr1, nfr2a, and creb1 genes in the brain of the Sco-induced zebrafish model.
Keywords: neurogenesis